Psychological adjustment and language development of young children in residential care - Pereira, Joana Campos (2020)
In Portugal, 98% children under the age of three removed from their birth families are living in Residential Care (RC) centres. The early placement of children in RC can dramatically affect their development. This study aims to: identify the frequency of internalizing, externalizing and total problems, as well as the average number of words used by young children in RC; compare the frequency of these children’s problems and their vocabulary to a Portuguese normative sample that allowed for the validation and standardization of the ASEBA Battery in Portugal; analyse differences among the children in RC according to gender, preschool integration, presence of siblings in the same RC centre, and the size of the RC centre itself and explore the correlations between the adjustment measures and language development and sociodemographic variables. One hundred and sixteen Portuguese children (56.9% female) ranging from 0 to 71 months (under 6 years) participated in this study. Data were collected using the ASEBA Battery. Results showed that these children presented a higher level of vulnerability regarding psychological adjustment and language development, when compared to children living within families, especially those separated from their siblings and living in a context which was not able to provide enough contact with other children. These findings highlight the importance of adopting measures such as family foster care (instead of RC), especially at this age, in order to give these children the chance of living in a normative and family context.